ANALISIS LARANGAN TRANSAKSI SHORT SELLING PADA PASAR MODAL SYARIAH SERTA DAMPAK NEGATIF YANG DITIMBULKAN DALAM PASAR MODAL KONVENSIONAL - Firdaus, Bilqis Annisa (Jurnal Akuntansi AKUNESA, 2014)
Islamic capital market is for investors who want to play by the rules of the shares in accordance with the Islamic Shariah. There are some transactions that are prohibited in the Islamic capital market, but are allowed in conventional capital markets, one of which is a transaction that is based on speculation that short selling or in the Islamic world known as bai'u maalaisa bimamluk. Prohibition of transactions is not only not in accordance with Islamic sharia, but can also cause great harm if the speculation is not appropriate.KEYWORDS: Islamic capital market, conventional capital markets, short selling